2008
DOI: 10.5254/1.3548206
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Investigation of Surface Modification of Carbon Black and Silica by Plasma Polymerization

Abstract: Carbon black and silica are widely used active fillers in the rubber industry to improve the physical and dynamic properties of rubbers. The surface energy difference between rubbers and these active fillers is large, which has a negative influence on the stability of their dispersion in the rubber matrix and on the distribution in blends of different rubbers. Reduction of the surface energy of carbon black and silica is aimed for by modifying their surfaces. Plasma polymerization is utilized to modify the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…For pure plasma-polymerized acetylene, decomposition starts at 2658C and is complete at 6008C. 26 The PA-silica shows 6 wt% loss in comparison with untreated silica.…”
Section: Characterization Of Pa Plasma-coated Relative To Untreated Smentioning
confidence: 99%
“…For pure plasma-polymerized acetylene, decomposition starts at 2658C and is complete at 6008C. 26 The PA-silica shows 6 wt% loss in comparison with untreated silica.…”
Section: Characterization Of Pa Plasma-coated Relative To Untreated Smentioning
confidence: 99%
“…It was suggested that plasma polymerization could be used to modify the surface of CB by depositing a thin film of polymer over it. 47 Fullerene soot, as a by-product of fullerene production, can be used in this plasma modification process. 48 In this case, both the CB and the polymer matrix had a comparable surface energy, where the polymer matrix could be an elastomer, such as styrene-butadiene rubber (SBR), butadiene rubber (BR) or ethylene-propylene diene rubber (EPDR), which are widely used in polymer bonded explosives (PBXs) and propellants.…”
Section: Carbon Molecules Graphyenesmentioning
confidence: 99%
“…Those filler particles could also be modified by the nitrogen plasma. In fact, some studies [49][50][51][52][53] consider the modification of fillers in rubbers (silica and carbon black) by plasma treatment and its influence in the rubber-filler interaction. Anyway, the modification of the surface energy of the filler exposed to the plasma after ablation mechanism and Table 5 Atomic percentages obtained for as received and 2 min plasma treated SW and ZS rubbers Binding energy (eV) its contribution to adhesion properties is likely less important than the contribution of the plasma treated rubber surface energy.…”
Section: Resultsmentioning
confidence: 99%